Development of Carbocyanine Dyes for PRMT Inhibition and Imaging - Sinha, Sarmistha Halder (2012)
Protein arginine methylation regulates multiple biological processes. Deregulation of protein arginine methyltransferase (PRMT) activities has been observed in many disease phenotypes. Small molecule probes that target PRMTs with strong affinity and selectivity can be used as valuable tools to dissect biological mechanisms of arginine methylation and establish the role of PRMT proteins in a disease process. In this work, we report synthesis and evaluation of a class of carbocyanine compounds containing indolium, benz[e]indolium or benz[c,d]indolium heterocyclic moieties that bind to the predominant arginine methyltransferase PRMT1 and inhibit its methyltransferase activity at low micromolar potencies. In particular, the developed molecules have long wavelength colorimetric and fluorometric photoactivities, which can be used for optical and near-infrared fluorescence imaging in cells or biological tissues. Together, these new chemical probes have potential application in PRMT studies both as enzyme inhibitors and as fluorescent dyes for microscope imaging.